2017
DOI: 10.1111/iji.12342
|View full text |Cite
|
Sign up to set email alerts
|

Association between killer cell immunoglobulin‐like receptor 2DS5 gene with essential hypertension in the Chinese Han patients

Abstract: Hypertension has been suggested to be mediated by immunity and inflammation. As immune system genes, killer cell immunoglobulin-like receptors (KIRs) genes play an important role in the pathogenesis of autoimmune diseases. We conducted a community population-based case-control study to analyse associations between KIR genes and hypertension. KIR genes were genotyped using sequence-specific primer polymerase chain reaction in 380 unrelated essential hypertensives and 527 normotensives. The frequencies of KIR2DS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
(47 reference statements)
0
3
1
Order By: Relevance
“…However, we did not detect any significant difference in the expression of these genes between diabetics and non-diabetics among our study participants. While our results showed a significant difference in the frequency of KIR2DL3 between hypertensive and normotensive HIV-positive individuals, Wang et al reported a significant association between the expression of KIR2DS5 and decreased risk of hypertension [ 44 ]. While our data did not reveal any association between the expression of KIR genes and risk of non-AIDS comorbidities, this could be due to ethnicity, sample size, and the population under study.…”
Section: Discussioncontrasting
confidence: 74%
See 3 more Smart Citations
“…However, we did not detect any significant difference in the expression of these genes between diabetics and non-diabetics among our study participants. While our results showed a significant difference in the frequency of KIR2DL3 between hypertensive and normotensive HIV-positive individuals, Wang et al reported a significant association between the expression of KIR2DS5 and decreased risk of hypertension [ 44 ]. While our data did not reveal any association between the expression of KIR genes and risk of non-AIDS comorbidities, this could be due to ethnicity, sample size, and the population under study.…”
Section: Discussioncontrasting
confidence: 74%
“…Several studies reported on KIR genes expressions among individuals with chronic conditions such as diabetes [ 42 ], hypertension [ 44 ], malignancies (colorectal cancer [ 65 ], biliary cancer [ 32 ], breast cancer [ 66 ], and leukemia [ 67 , 68 ]), and primary immunodeficiency disorders such as common variable immune deficiency (CVID) [ 69 ]. While the frequency of KIR genes did not differ between diabetics and healthy controls among the Chinese Han [ 70 ], Basque [ 71 ], and Saudi populations [ 72 ], the expression of KIR2DL3 was significantly different among British HIV-naïve children (<5 years) with type 1 diabetes compared to healthy controls [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations